2018
DOI: 10.1002/jcb.26599
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and exosomes in depression: Potential diagnostic biomarkers

Abstract: Depression is known as one of important psychiatric disorders which could be associated with disability among various populations. Diagnostic and statistical manual of mental disorders, 4th edition (DSM-IV) and international statistical classification of diseases and related health problems (ICD-10) could be used as subjective diagnostic schemes for identification of mental disorders such as depression. Utilization of subjective diagnostic schemes are associated with limitations. Hence, it seems that employing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 136 publications
(102 citation statements)
references
References 90 publications
0
101
0
1
Order By: Relevance
“…miRNAs are a negative regulator of translation by binding to mRNAs 3′‐UTR . Emerging evidence suggested that miRNAs might play the key role in regulating the process of neurotrophin, serotonergic signalling and synaptic plasticity process . Our results showed that chronic stress could up‐regulate the levels of miR‐15b‐5p, miR‐144‐3p and miR‐879‐5p expression (Figures ) as well as down‐regulate the expression of Gad1, VGAT and GAT‐3 genes and proteins, which impaired GABA tone.…”
Section: Discussionmentioning
confidence: 62%
“…miRNAs are a negative regulator of translation by binding to mRNAs 3′‐UTR . Emerging evidence suggested that miRNAs might play the key role in regulating the process of neurotrophin, serotonergic signalling and synaptic plasticity process . Our results showed that chronic stress could up‐regulate the levels of miR‐15b‐5p, miR‐144‐3p and miR‐879‐5p expression (Figures ) as well as down‐regulate the expression of Gad1, VGAT and GAT‐3 genes and proteins, which impaired GABA tone.…”
Section: Discussionmentioning
confidence: 62%
“…; Tavakolizadeh et al . ). Previously, we showed that a variety of miRNAs are involved in glioblastoma pathogenesis (Masoudi et al .…”
Section: Astrocytoma and Glioblastomamentioning
confidence: 97%
“…MicroRNAs are small non‐coding RNAs which act as epigenetic regulators . These molecules play critical roles in regulation of gene expression in the RNA and protein levels .…”
Section: Microrna and Exosome‐based Vaccinementioning
confidence: 99%